2002
DOI: 10.1103/physreva.66.062502
|View full text |Cite
|
Sign up to set email alerts
|

Spectral line shape of theP(2)transition in CO-Ar: Uncorrelatedab initiocalculation

Abstract: We calculate the spectral line shape of an isolated line from first principles, assuming that the translational motion is not statistically correlated with the evolution of the optical coherence, i.e., with the broadening. We use the known, realistic potentials for the influence of collisions on the translational motion and on the internal motion. We show that the calculated profiles do not agree, particularly at low pressures, with very precise experimental profiles of the P(2) line of CO in a bath of Ar. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
88
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(103 citation statements)
references
References 26 publications
12
88
1
Order By: Relevance
“…This may be associated with low rotational quantum number J of states corresponding to this transition (see Table 1). It was also reported by Duggan et al [16] and later confirmed by Wehr et al [53] that speed-dependent effects play more important role in case of transitions involving low than high J number states, and our simplified form of speed-dependencies is more clearly seen here than for other lines. The analysis presented above leads to a conclusion that exact speed-dependence of c L and D must be known to find reliable values of frequency of velocity changing collisions m H in the case of investigated H 2 O lines perturbed by Xe.…”
Section: Line Narrowing Analysissupporting
confidence: 81%
“…This may be associated with low rotational quantum number J of states corresponding to this transition (see Table 1). It was also reported by Duggan et al [16] and later confirmed by Wehr et al [53] that speed-dependent effects play more important role in case of transitions involving low than high J number states, and our simplified form of speed-dependencies is more clearly seen here than for other lines. The analysis presented above leads to a conclusion that exact speed-dependence of c L and D must be known to find reliable values of frequency of velocity changing collisions m H in the case of investigated H 2 O lines perturbed by Xe.…”
Section: Line Narrowing Analysissupporting
confidence: 81%
“…(8), we can attribute any b m 6 b d to correlation between velocity-changing and dephasing collisions [3]. Here, only the self-collisions yield b m > b d , which is normally a signal of speed-dependent broadening [8,11,25]. When speeddependent broadening is included for the sdR profile, the Dicke-narrowing coefficients show a drastic reduction for the foreign-gas cases, but an unusual increase for self-collisions.…”
Section: Dicke Narrowing and Speed-dependent Broadeningmentioning
confidence: 90%
“…Ideally, the speed dependence of the broadenings and shifts can be calculated either semiclassically or quantum-mechanically from realistic interaction potentials. However, this has been done for only a few simple cases such as HF-Ar [23,24] and CO-Ar [25]. Therefore, we use the classical-path R Àq potential model of Berman [9] and Ward et al [10].…”
Section: Lineshape Modelsmentioning
confidence: 99%
“…These effects have been observed for CO line shapes in a number of high-resolution studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], motivated in part by the need to monitor this species accurately in the earth and planetary atmospheres. Most of the CO line shape measurements have been reported for the v ¼ 1 0 fundamental band in a variety of buffer gases using a tunable differencefrequency laser [13][14][15][16][17][18][19][20] or diode laser [21,22]. In addition, microwave data for pure rotational lines [23][24][25][26] as well as Fourier-transform [27][28][29] and diode laser [30] spectra of the overtones have exhibited non-Voigt profiles.…”
Section: Introductionmentioning
confidence: 94%